The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1007/s00590-013-1252-8
|View full text |Cite
|
Sign up to set email alerts
|

Surgical site infection after open reduction and internal fixation of tibial plateau fractures

Abstract: Both open fracture and operative time are independent risks factors for postoperative infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
69
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(76 citation statements)
references
References 26 publications
5
69
2
Order By: Relevance
“…Although several studies had showed fine functional outcomes in the use of this approach, the incision related complications had not been systematically reported. The complication rate observed in this study showed a dominant advantage partially might benefit from good muscle in this approach over other posterior approaches (complication rate 4.7-23.6%) [8,9,[13][14][15]. Compared to the anterolateral aspects of the tibial plateau, there are layers of thick muscles in the posteromedial side of the knee, such as gastrocnemius and soleus, which can provide sufficient blood supply after incision and also, fully coverage of the implant.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Although several studies had showed fine functional outcomes in the use of this approach, the incision related complications had not been systematically reported. The complication rate observed in this study showed a dominant advantage partially might benefit from good muscle in this approach over other posterior approaches (complication rate 4.7-23.6%) [8,9,[13][14][15]. Compared to the anterolateral aspects of the tibial plateau, there are layers of thick muscles in the posteromedial side of the knee, such as gastrocnemius and soleus, which can provide sufficient blood supply after incision and also, fully coverage of the implant.…”
Section: Discussionmentioning
confidence: 80%
“…The high-energy tibial plateau fractures are difficult to be treated mostly for their high complications such as infection, nonunion and mechanical failure [8,9,[13][14][15], especially for those fractures with posterior fragments. Selecting an appropriate surgical approach was essential in the decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…Young and Barrack reported deep infection was present in 7 of 8 (87.5%; 95% CI 52.9-96.9%) bicondylar tibial plateau fractures treated with two plates through a midline incision [16]. A retrospective analysis showed that there were 11 of 109 (10.1%; 95% CI 4.4-15.8%) bicondylar tibial plateau fractures appeared surgical site infections after operation of ORIF [17]. Two incisions and two plates method reduced soft tissue irritation, the infection rates in which ranged from 0 to 22.3% in recent literature [18][19][20].…”
Section: Discussionmentioning
confidence: 96%
“…However, to make the scorecard simple and practical, we did not include all possible risk factors. The reported overall SSI rate associated with ORIF surgeries ranges from 5.2% to 16% [19,21,30,32]. Using our scoring method, about one third of our patients receiving ORIF procedures were identified as having a low SSI risk.…”
Section: Discussionmentioning
confidence: 97%